2017
DOI: 10.1249/mss.0000000000001299
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Assessment with the ActiGraph GT3X and Doubly Labeled Water

Abstract: Purpose To compare the degree to which four accelerometer metrics—total activity counts per day (TAC/d), steps per day (steps/d), physical activity energy expenditure (PAEE, kcal/kg/day), and moderate- to vigorous-intensity physical activity (MVPA, min/d)— were correlated with PAEE measured by doubly-labeled water (DLW). Additionally, accelerometer metrics based on vertical axis counts and triaxial counts were compared. Methods This analysis included 684 women and 611 men aged 43 – 83 years. Participants wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 39 publications
0
120
0
Order By: Relevance
“…The application of device-based measures of PA is evolving 17 ; our estimates of light and moderate-to-vigorous intensity activity duration have been evaluated and found to be reasonably accurate in comparison to a range of criterion measures. 15,16,18 To determine the volume of PA, we estimated intensity-specific activity counts-a metric demonstrated to be a good proxy for total volume of PA. 13 We also chose a widely accepted threshold to distinguish sedentary behavior from PA (100 AC) 19 and a light/moderate-tovigorous threshold designed to capture a broader range of lifestyle and ambulatory activities in adults (760 AC). 14 There are a variety of published cut points, 18 and NHANES studies have commonly used 2020 counts/min, which is based on ambulatory calibrations, to define moderate-to-vigorous PA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of device-based measures of PA is evolving 17 ; our estimates of light and moderate-to-vigorous intensity activity duration have been evaluated and found to be reasonably accurate in comparison to a range of criterion measures. 15,16,18 To determine the volume of PA, we estimated intensity-specific activity counts-a metric demonstrated to be a good proxy for total volume of PA. 13 We also chose a widely accepted threshold to distinguish sedentary behavior from PA (100 AC) 19 and a light/moderate-tovigorous threshold designed to capture a broader range of lifestyle and ambulatory activities in adults (760 AC). 14 There are a variety of published cut points, 18 and NHANES studies have commonly used 2020 counts/min, which is based on ambulatory calibrations, to define moderate-to-vigorous PA.…”
Section: Discussionmentioning
confidence: 99%
“…The devices were initialized to collect activity counts (AC) in 1‐minute epochs. Accumulated AC provide an accurate estimate of the duration and intensity of body movement at the waist and were summed across the whole day to assess total PA volume . Using established cut points, we summed the accumulated volume of activity as AC in nonsedentary light (100<AC<760) and moderate‐to‐vigorous activity (≥760 AC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Bland‐Altman analysis showed that the mean bias between measurements was −5 kcal/d (95% CI: −109 to 99 kcal/d). This method of estimating TDEE has similar accuracy compared to with other types of PA monitoring devices .…”
Section: Resultsmentioning
confidence: 74%
“…With the exception of vigorous-intensity physical activity, the day-to-day intraclass correlation for accelerometer counts estimated for at least three valid consecutive days was .80 (Supplementary Material [available online]). ActiGraph ® wGT3X-BT is a tri-axial accelerometer that has been found to be reliable in free-living situations (Aadland & Ylvisåker, 2015) and has been validated in adults using indirect calorimetry (Santos-Lozano et al, 2013) and doubly labelled water (Chomistek et al, 2017) as criterion measures.…”
Section: Methodsmentioning
confidence: 99%